2023
DOI: 10.1021/acs.jpclett.3c00786
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Effect in D2O Negative Ion Formation in Electron Transfer Experiments: DO–D Bond Dissociation Energy

Abstract: H2O/D2O negative ion time-of-flight mass spectra from electron transfer processes at different collision energies with neutral potassium yield OH–/OD–, O–, and H–/D–. The branching ratios show a relevant energy dependence with an important isotope effect in D2O. Electronic state spectroscopy of water has been further investigated by recording potassium cation energy loss spectra in the forward scattering direction at an impact energy of 205 eV (lab frame), with quantum chemical calculations for the lowest-lyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 76 publications
3
11
0
Order By: Relevance
“…From the resonant charge-exchange process and the slits apertures, the potassium beam is mainly composed of potassium atoms in the groundstate configuration with its outermost electron as 4 s. This is supported by the experimental thresholds of formation which otherwise would result in values at lower energies (see Section 3) if K* in a 4p state were to be a relevant contribution. This is in accord with previous energy loss data from potassium collisions with pyrimidine, [33] halothane, [46] tetrachloromethane [45] and more recently with hexachlorobenzene [36,47] and water [48] probed in our laboratory.…”
Section: Experimental and Theoretical Methodologiessupporting
confidence: 93%
“…From the resonant charge-exchange process and the slits apertures, the potassium beam is mainly composed of potassium atoms in the groundstate configuration with its outermost electron as 4 s. This is supported by the experimental thresholds of formation which otherwise would result in values at lower energies (see Section 3) if K* in a 4p state were to be a relevant contribution. This is in accord with previous energy loss data from potassium collisions with pyrimidine, [33] halothane, [46] tetrachloromethane [45] and more recently with hexachlorobenzene [36,47] and water [48] probed in our laboratory.…”
Section: Experimental and Theoretical Methodologiessupporting
confidence: 93%
“…The difference in the linear packing density of diazonium ions on the SWCNT surface, θ TA , is smaller (i.e., ∼1.98 times larger in D 2 O than in H 2 O) compared to the reaction constant K R (i.e., ∼18.2 times larger in D 2 O than in H 2 O), while the saturated extent of doping, A , is the same for reactions performed in both solvents (Table ). These results suggest that solvent isotope effects potentially impact the aryl diazonium reaction with SWCNTs, where the solvent waters participate in the reactions possibly through the breaking of O–H and O–D bonds, respectively. , It is also important to point out that D 2 O (deuteration degree of ≥99.9%) was used in SWCNT reactions. There is residual H 2 O, and some H 2 O might be introduced due to water absorption during sample preparation.…”
Section: Resultsmentioning
confidence: 98%
“…These results suggest that solvent isotope effects potentially impact the aryl diazonium reaction with SWCNTs, where the solvent waters participate in the reactions possibly through the breaking of O−H and O−D bonds, respectively. 48,49 It is also important to point out that D 2 O (deuteration degree of ≥99.9%) was used in SWCNT reactions. There is residual H 2 O, and some H 2 O might be introduced due to water absorption during sample preparation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, our group pioneered a general visible-light-driven strategy for deoxygenative radical functionalization of alcohols, upon the intermediacy of xanthate anions in the presence of phosphine. , Our further achievements have demonstrated that xanthate anions can be directly excited by visible light into potent single electron reductants, to allow deoxygenation of alkyl radicals from alcohols under mild and photocatalyst-free conditions. , On this basis, it is envisaged that the utilization of our xanthate-anion-mediated strategy could also enable the deoxygenative deuteration of alcohols with the most ideal deuterium source, D 2 O. Since direct hydrogen atom transfer from D 2 O to an alkyl radical is thermodynamically unfavorable due to the strong bond-dissociation energy (BDE) of the O–D bond, it was recognized that the choice of a suitable catalyst, enabling (1) efficient and precise deuterium atom transfer (DAT) and (2) effective electron transfer (ET) from the xanthate anion to generate a xanthate radical for subsequent fragmentation, would be crucial for the transformation. Most recently, in the extension of photoredox-catalyzed deoxygenative functionalization of alcohols via xanthate salts, Takemoto and co-workers showcased two cases of deoxygenative deuteration by employing a noble iridium photocatalyst, but with low yields and moderate deuterium incorporation (Scheme C) .…”
mentioning
confidence: 99%